The sex-specific effects of famine on the association between placental size and later hypertension - van Abeelen, A.F.M.; de Rooij, S.R.; Osmond, C.; Painter, R.C.; Veenendaal, M.V.E.; Bossuyt, P.M.M.; Elias, S.G.; Grobbee, D.E.; van der Schouw, Y.T.; Barker, D.J.P.; Roseboom, T.J. (Placenta (Eastbourne), 2011)
People who had low birth weight are at increased risk of hypertension. This may reflect fetal programming by undernutrition. Placental size is also associated with hypertension. Maternal undernutrition during the Dutch famine reduced placental surface area. We examined whether maternal undernutrition altered the relationship between placental size and later hypertension. Retrospective cohort study among 860 subjects born in Amsterdam during 1943–47. 216 subjects were taking anti-hypertensive medication. Birth records included placental length and breadth from which we calculated its area. Among men who were not in utero during the famine hypertension was associated with a small placental surface area due to a small placental breadth, and with an oval-shaped surface. The OR for hypertension was 0.83 (95% CI 0.70 to 1.00) for a 40 cm2 increase in surface area. Among men who were in utero during the famine hypertension was associated with a large placental surface area due to a large placental breadth, and with a round-shaped surface. The OR for hypertension was 1.34 (95% CI 0.99 to 1.80) for a 40 cm2 increase in surface area. The associations between placental size and hypertension in men who were and were not in utero during the famine were significantly different (p values for interaction = 0.008 for placental surface area, 0.001 for the breadth and 0.01 for the difference in the two diameters). Among women hypertension was not associated with placental size. Our study provides the first direct evidence that changes in maternal diet during pregnancy alter the relationship between placental size and later hypertension among men but not women. We suggest that among men who were not in utero during the famine, hypertension was related to impaired implantation, whereas among men who were in utero during the famine it was related to compensatory expansion of the placental surface.